2008
DOI: 10.1097/jom.0b013e31817e9171
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Psychological Distress in Employees and Associated Occupational Risk Factors

Abstract: High psychological distress is pervasive across all employee subtypes and remains largely untreated. Risk factors identified will guide the targeting of mental health promotion, prevention and screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
109
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 63 publications
3
109
1
2
Order By: Relevance
“…These types of work schedules can also lead to negative effects on family life and social isolation, which will further endanger the mental health of workers. All in all, work schedule and work hours increase the risk of psychological distress (Hayasaka et al 2007, Hilton et al 2008, Marchand, Demers, and Durand 2005b, Matthews, Power, and Stansfeld 2001, Sekine et al 2006, Spurgeon, Harrington, and Cooper 1997. Conflicting relationships at work, either with co-workers or supervisors, can create a stressful experience that may impact on the mental health of workers.…”
Section: Work Organisation Conditionsmentioning
confidence: 99%
“…These types of work schedules can also lead to negative effects on family life and social isolation, which will further endanger the mental health of workers. All in all, work schedule and work hours increase the risk of psychological distress (Hayasaka et al 2007, Hilton et al 2008, Marchand, Demers, and Durand 2005b, Matthews, Power, and Stansfeld 2001, Sekine et al 2006, Spurgeon, Harrington, and Cooper 1997. Conflicting relationships at work, either with co-workers or supervisors, can create a stressful experience that may impact on the mental health of workers.…”
Section: Work Organisation Conditionsmentioning
confidence: 99%
“…However, previous work has shown that the response rate does not correlate with prevalence of high K6. 5 Prior studies have shown that respondents and non-respondents to a HRA survey have comparable levels of depression. 62,64 Although the sample is non-random, and has a response rate of 25%, it is one of the largest samples of employees collected and the sheer volume of data infers a certain amount of validity.…”
Section: Limitationsmentioning
confidence: 99%
“…5,41 In brief, 58 large employers (more than 1,000 employees) agreed to participate in the study. HPQ surveys were circulated to employees of the participating organisations using either paper-based or webbased methods.…”
Section: Survey Design and Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long work hours may confer a strain that is detrimental to health (1)(2)(3)(4)(5)(6)(7)(8). A potential negative health effect of long work hours is the risk of depression (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%